On the last mile: logistical urbanism and the transformation of labour. (1st April 2019) - Altenried, Moritz
Abstract : In recent years, the last mile of delivery has become a crucial focus of logistical operations in urban contexts due to the rise of online shopping and the spread of platforms including Amazon to Foodora, Deliveroo and others. This article claims that the increasing importance and time-sensitivity of delivery reconfigures both urban spaces and labour relations. Through an analysis of labour relations in different segments of last mile delivery it argues that we are observing profound changes driven most importantly by digital technologies and the hyper-flexible employment relations facilitated by online platforms. Labour on the last mile is increasingly characterised by intense time pressure, standardisation, algorithmic management and digitally enabled surveillance on the one hand, and platform-driven precarisation and flexibilisation on the other. These developments can also be observed in other areas of logistical labour and across different industries. Hence, labour on the last mile might be understood as a specific but important expression of a broader tendency of the transformation of labour in digital capitalism. At the same time, the new importance of the last mile also signals changes in the production of urban space in the context of platform-driven forms of production, circulation and consumption, that are discussed as an emerging logistical urbanism.